Meta-synthesis of factors affecting the explanation of sales network performance in the Iranian insurance industry - Daghighi Asli, Hashem (2020)
The aim of this study was Meta-synthesis of factors affecting the explanation of sales network performance in the Iranian insurance industry. The method of this research using the data theory, which is one of the best research strategies, through which; Theory is based on the main concepts of the data. In this regard, the meta-combined method has been systematically used to collect and review previous studies and the foundation data method to provide a theoretical model. In the first stage, by integrating automatic and manual search strategies, 25 related research articles published in the scope of sales network performance in the insurance industry in the period 2009 to 2018 is covered for English articles and 2011 to 2018 for Persian articles. In the final stage, after implementing the proposed steps of Glaser and Strauss, the proposed theoretical model is presented. The results of the research obtained from the first stage have shown that psychological and behavioral factors have the highest frequency in previous studies and have paid the most attention, which in fact focuses studies on empowering human resources active in the insurance industry. According to the results individual factors related to representatives and factors related to the organization of representatives, central conditions including: performance of insurance agent, strategic conditions including: factors related to central insurance, prevailing context conditions included.